Does payroll tax affect firm behaviour? - Ben Ralston (The Australian Government, The Treasury, 2018)
Payroll tax has been frequently singled out as having an adverse effect on businesses and the economy in general. Payroll tax is levied by the States against the total sum of remuneration of employees within a firm for each dollar above a threshold. The threshold exempts small businesses from payroll tax. This could cause firms to try to avoid payroll tax by staying small and therefore bunching just below the threshold. To mitigate the potential distortions of payroll tax, the policy prescription is to have a low rate and a low threshold. This paper uses administrative business income tax data covering 2001-02 to 2014-15 to determine whether payroll tax affects the behaviour of businesses. The key observations that emerge are: 1. Firms generally do not bunch below the payroll tax threshold. 2. The limited bunching in Victoria, which had one of the lowest thresholds and one of the lowest tax rates during the sample period, is unexpected as Victoria had followed the policy prescription designed to mitigate the adverse effects of payroll tax. 3. Firms, in general, do not attempt to avoid payroll tax by hiring contractors.
Keywords: H25; 330; Payroll tax; business tax; bunching; distortionary tax